Notice, Consent, and Choice-of-Jurisdiction Clauses in the United States - John F. Coyle (German Law Journal)
Although choice-of-jurisdiction clauses are routinely enforced by courts in the United States, there are circumstances where they are subject to special scrutiny. One of these circumstances is when the party resisting the clause was not provided with proper notice as to the existence of the clause or the identity of the chosen jurisdiction. This Article first reviews the existing case law in this area and shows that while some U.S. courts have refused to enforce clauses for lack of notice, others do so as a matter of course. It then discusses several decisions where U.S. courts have held that notice may serve as a substitute for consent to bind parties to choice-of-jurisdiction clauses in agreements that they never signed.